MODERN ACCOUNTING SYSTEM IN THE CONTEXT OF ITS POLYFUNCTIONALITY - Кундря-Висоцька , Оксана; Любенко, Андрій; Демко, Ірина (Socio-economic relations in the digital society, 2019)
The article substantiates the necessity of adjusting and supplementing the functions of the information cycle in the accounting system in order to deepen the links between the accounting function and other functions of the management cycle: planning, economic analysis, control, etc. It is proved that signifi cant changes in the methodological approaches to accounting that occurred as result of its reform. As well as the high degree of standardization of accounting methodology, its conservatism, lack of efficiency of making changes to the organizational and methodical components of the accounting process, the inconsistency of accounting information with changing conditions for the adoption of economic decisions require revision of the conceptual functional components of the accounting system. The tendencies of the development of accounting functions in the context of the evolution of social development, as well as the direct influence of the integration processes in the economy of the subject of management on the integration changes within the accounting system itself are analyzed. It is proved that the result of the implementation of such multifunctionality of the accounting system is, in the end, an algorithm for the formation of a particular accounting model in enterprises of diff erent forms of management. As a consequence of the multifunctionality of the accounting system, the expansion of the accounting methodology at the level of elements of its method by identifying additional objects of assets, capital, liabilities, income, expenses and other facts of economic activity; application of additional methods and procedures for data processing, including nonfi nancial information; the preparing of untypical forms of statements that correspond to the information requests of management staff or are of public interest. It is confirmed that for accounting, as a complex socially-conditioned system, the purpose is from the outside and changes and develops in accordance with the tendencies of the development of the management system. Trends in the development of the management system, the complication of its mechanisms, the emergence of qualitatively new subjects and objects in the market conditions necessitate the expansion of the range of accounting tasks and, accordingly, the evolution of its functions in the direction for the satisfaction of management requests at diff erent levels.